Pharmacokinetics of cephalosporins in the neonate: a review - Gian Maria Pacifici (Clinics, 2011)
The aim of this work was to review the published data on the pharmacokinetics of cephalosporins in neonates to provide a critical analysis of the literature as a useful tool for physicians. The bibliographic search was performed for articles published up to December 3, 2010, using PubMed. In addition, the book Neofax: A Manual of Drugs Used in Neonatal Care by Young and Mangum was consulted. The cephalosporins are mainly eliminated by the kidneys, and their elimination rates are reduced at birth. As a consequence, clearance is reduced and t1/2 is more prolonged in the neonate than in more mature infants. The neonate's substantial body water content creates a large volume of distribution (Vd) of cephalosporins, as these drugs are fairly water soluble. Postnatal development is an important factor in the maturation of the neonate, and as postnatal age proceeds, the clearance of cephalosporins increases. The maturation of the kidney governs the pharmacokinetics of cephalosporins in the infant. Clearance and t1/2 are influenced by development, and this must be taken into consideration when planning a cephalosporin dosage regimen for the neonate.